2018
DOI: 10.1111/ele.12964
|View full text |Cite
|
Sign up to set email alerts
|

Topography shapes the structure, composition and function of tropical forest landscapes

Abstract: Topography is a key driver of tropical forest structure and composition, as it constrains local nutrient and hydraulic conditions within which trees grow. Yet, we do not fully understand how changes in forest physiognomy driven by topography impact other emergent properties of forests, such as their aboveground carbon density (ACD). Working in Borneo - at a site where 70-m-tall forests in alluvial valleys rapidly transition to stunted heath forests on nutrient-depleted dip slopes - we combined field data with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

13
284
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 267 publications
(298 citation statements)
references
References 70 publications
(197 reference statements)
13
284
1
Order By: Relevance
“…). For example, plots in the landscape‐scale UMBS‐LE data set showed separation into four different CSTs (Fig b), reflecting the strong influence that fine‐grain variation in physiographic factors can have on canopy structural development and that CSTs are integrators of these environmental factors (Aber et al ; Dial et al ; Kane et al ; Nave et al ; Jucker et al ). In addition, the successional chronosequences at UMBS spanned five CSTs and included variation, largely driven by stand age, equivalent to that present in the entire sub‐continental LQ‐NEON data set.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…). For example, plots in the landscape‐scale UMBS‐LE data set showed separation into four different CSTs (Fig b), reflecting the strong influence that fine‐grain variation in physiographic factors can have on canopy structural development and that CSTs are integrators of these environmental factors (Aber et al ; Dial et al ; Kane et al ; Nave et al ; Jucker et al ). In addition, the successional chronosequences at UMBS spanned five CSTs and included variation, largely driven by stand age, equivalent to that present in the entire sub‐continental LQ‐NEON data set.…”
Section: Discussionmentioning
confidence: 99%
“…However, the arrangement of ecosystems among and within these broad categories of CSTs is also likely to be related to fine-scale environmental variation (e.g. soil water holding capacity, topography; Aber et al 1982;Jucker et al 2018), species, crown type, PFT, and trait composition of the local community (Ishii & Asano 2010;Verbeeck et al, 2019), stand to landscape-level community characteristics (e.g. alpha and beta diversity; Dial et al 2004;Jucker et al 2015) and historical factors such as successional processes and disturbance legacies (Scheuermann et al 2018).…”
Section: Introductionmentioning
confidence: 99%
“…In addition to these interactive effects between aspect and canopy height, we also found clear evidence that topography can influence understorey microclimate indirectly by driving fine-scale variation in forest structure within tropical landscapes. Previous work has highlighted the importance of topography in shaping the composition and structure of forest canopies (Jucker, Bongalov, et al, 2018;Swetnam, Brooks, Barnard, Harpold, & Gallo, 2017;Werner & Homeier, 2015), but to our knowledge, the implications of this for understorey microclimate have been largely overlooked. We found that across the SAFE landscape canopy height varied substantially in relation to terrain elevation, slope aspect and curvature (see Appendix S4).…”
Section: Canopy Structure and Topography As Drivers Of Understoreymentioning
confidence: 99%
“…This influence can be synthesized in the Topographic Wetness Index (TWI; Gessler, Moore, McKenzie, & Ruan, ; Sørensen, Zinko, & Seibert, ). The topographic variation then influences the structure, composition and functioning of tropical forests (Cheesman, Preece, van Oosterzee, Erskine, & Cernusak, ; Fortunel et al., ; Jucker et al., ; Svenning, ; Valencia et al., ). On upslopes or steep slopes, tree communities generally show more conservative strategies (Cheesman et al., ; Kraft et al., ; Liu, Yunhong, & Slik, ; McFadden et al., ) and/or denser wood (Jucker et al., ; Liu et al., ).…”
Section: Introductionmentioning
confidence: 99%